2016
DOI: 10.21474/ijar01/399
|View full text |Cite
|
Sign up to set email alerts
|

LCMS/MS analysis of methanolic rhizome extracts of Alpinia calcarata Roscoe (Zingiberaceae) -A multipotent medicinal plant.

Abstract: Alpinia calcarata Rosc. of Zingiberaceae popularly known also as Lesser galangal has a widespread occurrence in India, Malaysia, Bangladesh and China. Drugs prepared by using rhizomes of Alpinia calcarata are used in the treatment of rheumatism, bronchial catarrah and asthma. They are also used against infection of the skin and also possess antibacterial activity. LCMS/MS study has provided chemical profile present in the methanolic rhizome extract. LCMS/MS full scan was performed on ESI ionization mode using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Similarly, the major components found in the leaf powder sample were the epidermal cells, parenchymal cells, xylem vessels, crystal fibers, and calcium oxalate crystals. Nonetheless, the red-brown oleoresin masses are not found in the C. vietnamense leaf powder, a result similar to that of A. calcarata and A. galanga (Mathew et al 2014). However, these oleoresin masses are found in G. marantina (Roy et al 2016) As a result of the study of C. vietnamense rhizome and leaf powders composition, it can be suggested that the absence of epidermal and parenchymatous cells, solidshaped calcium oxalate crystals, thick-walled crystal fiber, egg-shaped or pear-shaped starch granules, spiral xylem vessel, reticulate xylem vessel, and red-brown oleoresin masses in the rhizome powder samples, as well as the absence of epidermal and parenchymatous cells, spiral xylem vessel, solid-shaped and square-shaped calcium oxalate crystals, thick-walled crystal fiber in the leaf powder samples; all of these ingredients will aid in the identification of deliberate or unintentional adulteration with the raw powder.…”
Section: Leaf Powdermentioning
confidence: 54%
“…Similarly, the major components found in the leaf powder sample were the epidermal cells, parenchymal cells, xylem vessels, crystal fibers, and calcium oxalate crystals. Nonetheless, the red-brown oleoresin masses are not found in the C. vietnamense leaf powder, a result similar to that of A. calcarata and A. galanga (Mathew et al 2014). However, these oleoresin masses are found in G. marantina (Roy et al 2016) As a result of the study of C. vietnamense rhizome and leaf powders composition, it can be suggested that the absence of epidermal and parenchymatous cells, solidshaped calcium oxalate crystals, thick-walled crystal fiber, egg-shaped or pear-shaped starch granules, spiral xylem vessel, reticulate xylem vessel, and red-brown oleoresin masses in the rhizome powder samples, as well as the absence of epidermal and parenchymatous cells, spiral xylem vessel, solid-shaped and square-shaped calcium oxalate crystals, thick-walled crystal fiber in the leaf powder samples; all of these ingredients will aid in the identification of deliberate or unintentional adulteration with the raw powder.…”
Section: Leaf Powdermentioning
confidence: 54%
“…Phytochemical analysis of the Alpinia calcarata rhizomes extracted using soxhlet apparatus with different solvents revealed the presence of polyphenols, tannins, flavonoids, steroid, glycosides and alkaloids [1]. Beta alanine, isovaleric acid, catechol, citral protocatechuic acid, iso menthone, nerol umbelliferone, chrysin, apigenindi-methyl ether, vanillic acid, myristic acid, acetoxycha-vicol acetate, nerolidol, himachalol, dihydro resveratrol, confertin, valerenic acid, alpha-linolenic acid isolated from rhizomes of methanolic extract of Alpinia calcarata by LCMS/MS analysis [2].…”
Section: Discussionmentioning
confidence: 99%
“…Alpinia calcarata is used in the oriental part of the world as a food additive, spice and in indigenous system of medicine. It grows in dense forests at high altitudes and is considered as a native of India [2]. Alpinia calcarata rhizomes are branched and dense with a light to dark brown colour and known to possess a broad spectrum of medicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Selain biji, anatomi rimpang antar jenis Alpinia bervariasi juga. Rimpang Alpinia calcarata memiliki butir pati melonjong dan jaringan parenkim penyusun korteks tanpa berkas pembuluh, sedangkan rimpang A. galanga memiliki butir pati membulat dan jaringan parenkim penyusun korteks dijumpai banyak berkas pembuluh (Mathew, Britto, & Thomas, 2014). Anatomi daun kedua jenis juga berbeda pada ciri berkas pembuluh xilem (pada A. galanga ditutupi oleh floem), dan posisi berkas pembuluh (saling campur pada A. calcarata).…”
Section: Pendahuluanunclassified
“…Anatomi daun kedua jenis juga berbeda pada ciri berkas pembuluh xilem (pada A. galanga ditutupi oleh floem), dan posisi berkas pembuluh (saling campur pada A. calcarata). Namun, daun kedua jenis tersebut memiliki persamaan pada ciri jumlah lapisan sel penyusun epidermis dan hipodermis (hanya berjumlah satu lapis), bentuk sel parenkim penyusun bagian korteks (tanpa ruang antar selular), dan kedudukan sel sklerenkim (mengelilingi kelenjar pembuluh) (Mathew et al, 2014).…”
Section: Pendahuluanunclassified